Impact of studying economics on labor development: the National Agrarian University La Molina case - Trujillo Cubillas, Humberto Alejandro (2022)
The understanding the job development of university graduates will allow adjusting the study plans of new students to successfully face the labor market. In this sense, this research explores the impact of studying economics on graduates of this career at the La Molina National Agrarian University. Information was collected from surveys carried out between 2019 and 2021 by the career administration, to which data cleaning procedures and cluster analysis were applied. The study resulted in three clusters: the first is made up of graduates who studied under the 2012 Study Plan and are mostly entrepreneurs, are not linked to their career, are satisfied with their studies and have average salaries. The other two clusters are made up of graduates trained under the 2001 Study Plan: the second cluster groups those linked to their careers, satisfied with their studies and who receive high salaries; the third cluster groups those who are not linked to their career, have low incomes and whose highest proportion was looking for a job. Although the graduates of the second and third cluster come from the 2001 Study Plan, their work results and satisfaction with their career are different: those who are most linked to their careers are those with the best work results and greatest satisfaction.